Interleukin-15 enhances the expansion and function of natural killer T cells from adult peripheral and umbilical cord blood. Issue 2 (December 2015) - Lin, Syh-Jae; Huang, Ying-Cheng; Cheng, Po-Jen; Lee, Pei-Tzu; Hsiao, Hsiu-Shan; Kuo, Ming-Ling
Highlights: First study to demonstrate the expansion of iNKT cells from umbilical cord blood. IL-15 enhances α-GalCer-induced expansion of iNKT cells from adult or cord blood. IL-15 decreases early apoptosis and enhances IFN-γ production by iNKT cells. IL-15 enhances perforin expression and NK cytotoxicity of expanded iNKT cells. IL-15 benefits post-UCB transplant period when iNKT function remains poor. Abstract: Invariant natural killer T cells (iNKT cells) are innate-like non-conventional T cells restricted by the CD1d molecule that are unique in their ability to play a pivotal role in immune regulation. Deficient iNKT function has been reported in patients receiving umbilical cord blood (UCB) transplantation. We sought to determine the effect of interleukin (IL)-15 on α-galactosylceramide (α-GalCer)-expanded iNKT cell function from UCB and adult peripheral blood (APB) mononuclear cells (MNCs). Fresh APB and UCB MNCs were cultured with IL-15 (50 ng/ml) in the presence or absence of α-GalCer (100 ng/ml) for 10 days. Cells were harvested for examination of cell yield, apoptosis, cytokine production and cytotoxic function of Vα24 + /Vβ11 + iNKT cells. We observed that α-GalCer-expanded APB and UCB iNKT cells and such expansion was further enhanced with IL-15. The percentage of CD3 + CD56 + NKT-like cells in both APB and UCB MNCs was increased with IL-15 but not with α-GalCer. Apoptosis of UCB iNKT cells was ameliorated by IL-15. Although APB and UCB iNKT cells secreted lower IFN-γ, it could be enhanced with IL-15. The expression of perforin in APB iNKT cells can also be enhanced with IL-15. UCB Vα24 + Vβ11 + iNKT cells further augmented K562 cytotoxicity mediated by IL-15. Taken together, these results demonstrated the relative functional deficiencies of α-GalCer induced UCB iNKT cells, which can be ameliorated by IL-15. Our findings suggest a therapeutic benefit of IL-15 immunotherapy during the post-UCB transplant period when iNKT function remains poor.